2013
DOI: 10.5812/numonthly.13351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C Supplementation on C-reactive Protein Levels in Patients Undergoing Hemodialysis: A Randomized, Double Blind, Placebo-Controlled Study

Abstract: Background:Chronic inflammation is the most important cause of cardiovascular disease in patients undergoing hemodialysis, and vitamin C as a major antioxidant which could be effective to suppress inflammation.Objectives:This study was performed to evaluate the effect of vitamin C supplementation on C-reactive protein levels in patients undergoing hemodialysis.Patients and Methods:This randomized, placebo-controlled and double-blind trial was conducted on 151 patients on hemodialysis who were divided randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
1
14
4
Order By: Relevance
“…When high level (> 6mg/l) comparison with low level (<6 mg/l) of CRP in relation to haemodialysis in the current study, there was 52.5% of the patients had high (>6mg/l) CRP level ( Table 6). This result is higher than that reported by Korevaar et al,29 in which this prospective multicenter study on the impact of an HD session on CRP level showed an increase in CRP level in 25% of the patients during a dialysis session. Moreover, independent of the pre-dialysis CRP level, the change in CRP level during an HD session was associated with an increased mortality risk; an increase of 1 mg/l in CRP level was associated with a 9% raised mortality risk.…”
Section: Discussioncontrasting
confidence: 74%
“…When high level (> 6mg/l) comparison with low level (<6 mg/l) of CRP in relation to haemodialysis in the current study, there was 52.5% of the patients had high (>6mg/l) CRP level ( Table 6). This result is higher than that reported by Korevaar et al,29 in which this prospective multicenter study on the impact of an HD session on CRP level showed an increase in CRP level in 25% of the patients during a dialysis session. Moreover, independent of the pre-dialysis CRP level, the change in CRP level during an HD session was associated with an increased mortality risk; an increase of 1 mg/l in CRP level was associated with a 9% raised mortality risk.…”
Section: Discussioncontrasting
confidence: 74%
“…After the study period, compared to controls, the Vitamin C group exhibited a significant decrease in serum uric acid concentrations [78]. Moreover, Vitamin C supplementation resulted in a significant decrease of circulating CRP levels [79]. The authors concluded that since HD is a state of enhanced OS and inflammation characterized by decreased antioxidant activity and high incidence of hyperuricemia, Vitamin C supplementation could have multiple beneficial effects in chronic HD patients.…”
Section: Vitamins C and Ementioning
confidence: 99%
“…Therefore, it is not clear if there are sex specific effects. As intervention studies are usually conducted on diseased or high-risk samples ( 5 9 ) , conclusions cannot be drawn from them for the general healthy population. Moreover, it is possible that effects of intakes of single nutrients differ from those of combined intakes, because nutrients might interact with each other.…”
mentioning
confidence: 99%